2016
DOI: 10.1038/srep22642
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen acquisition by plants and microorganisms in a temperate grassland

Abstract: Nitrogen (N) limitation is common in most terrestrialPlants and microorganisms compete for the same soil resources, but they are mutually dependent on each other 1 . Soil microorganisms need labile organic substances from plants in the form of litter and root exudates 2-4 to mineralize nutrients from organic to inorganic forms. Plants rely on nutrient supplies mediated by soil microorganisms 4-6 . Plant productivity and soil microbial activities are often tightly coupled, especially in nutrient-poor ecosystems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 52 publications
3
35
1
Order By: Relevance
“…The lower soil NO 3 − content in the NT plots could result from a greater uptake by soil microorganisms. Moreover, it has been shown that substantial amounts of soil inorganic N can be taken up by microorganisms [15] and that NT enhances microbial biomass as compared to conventional tillage (CT) [16]. Another hypothesis is that increased mineralization of soil organic matter pools, caused by the annual moldboard ploughing [17,18], leads to an accumulation of NO 3 − in CT plots.…”
Section: Resultsmentioning
confidence: 99%
“…The lower soil NO 3 − content in the NT plots could result from a greater uptake by soil microorganisms. Moreover, it has been shown that substantial amounts of soil inorganic N can be taken up by microorganisms [15] and that NT enhances microbial biomass as compared to conventional tillage (CT) [16]. Another hypothesis is that increased mineralization of soil organic matter pools, caused by the annual moldboard ploughing [17,18], leads to an accumulation of NO 3 − in CT plots.…”
Section: Resultsmentioning
confidence: 99%
“…(2019), the N deficiency remains as the main limitation of rice yield with adoption of no‐tillage alone. Normally, N is the most limiting nutrient in systems with high residue amounts, and this is due to the greater advantage and capacity of the soil microorganisms for N uptake compared with plant roots across any concentration range (Geisseler, Horwath, Joergensen, & Ludwig, 2010; Kuzyakov & Xu, 2013; Liu et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Higher yields observed under ICLS are also possibly related to greater synchronism between N uptake by rice and N released from soil and microorganisms (because immobilized N becomes available for rice after death of microorganisms) compared with CS (Kuzyakov & Xu, 2013; Liu et al., 2016). Short immobilization of mineral N by microorganisms is an important adaptation of ecosystems, and the allocation of N within soil microorganisms protects against losses, such as N leaching or denitrification (Kuzyakov & Xu, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…, Kaye and Hart , Liu et al. ). Microbial processes responsible for mineralization and nitrification of NH 4 + and NO 3 − are sensitive to soil moisture and temperature, with temperature sensitivity depending on soil moisture (Sierra , Tian et al.…”
Section: Introductionmentioning
confidence: 99%
“…These changes are likely the result of alterations to the timing and variability of available resources, particularly soil water and inorganic nitrogen (NH 4 + /NO 3 À ). Research suggests that plants and microbes are commonly limited by inorganic nitrogen, even on relatively fertile soils (Zak et al 1990, Kaye and Hart 1997, Liu et al 2016. Microbial processes responsible for mineralization and nitrification of NH 4 + and NO 3 À are sensitive to soil moisture and temperature, with temperature sensitivity depending on soil moisture (Sierra 1997, Tian et al 2010, Guntiñas et al 2012, Li et al 2014, Wang and Loreau 2016.…”
Section: Introductionmentioning
confidence: 99%